PHILOSOPHY OF SCIENCE AND RECONSTRUCTION OF CLAS VIRTUAL MODEL THEORY COMPUTER MATHEMATICS (International Conference on Social and Islamic Studies, 2022)
This study aims to determine the process of developing Virtual Class learning media. The material is presented in the form of an interactive model using the Learning Center Area.  V-Class is an alternative means in the web-based learning process in the form of supplements/additions from e-learning learning applications. The V-Class application that will be made is expected to be an alternative to additional learning media, in addition to books to facilitate the teaching and learning process, and even useful as a means of communication between students and lecturers and between students. This research uses a Research and Development (R&D) model with an Analysis, Design, Development, Implementation, and Evaluation model. The product developed is a virtual class learning model.  The results of the comparison will show the advantages and disadvantages of the existing Learning Management System, making it easier for lecturers to choose a Learning Management System application that is considered appropriate for lecture needs.